2009
DOI: 10.2485/jhtb.18.135
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Apatite Crystals Formed During Vascular Calcification in Humans

Abstract: :Using a transmission electron microscope, we compared the ultrastructure of apatite crystals of normal calcified hard tissue to that of apatite crystals created under pathological conditions. We also sought to verify whether the process of calcification resembles that of osteogenesis after the phenotypic change of soft tissue cells into hard tissue-forming cells. Electron micrographs clearly revealed that cellular debris, plausibly originating from degenerated immune cells like macrophages as well as perivasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Our Raman analysis, however, revealed that the replacement of OH with F ions did not occur in rat developing enamel (Table I). This finding may be due to 2 different calcification mechanisms whereby the formation of crystal either with CDL or without CDL is strictly regulated by each hard tissue with the except of pathological calcification 44) . One pathway, mediated by the precursor mineral octacalcium phosphate (OCP), may have appeared around the Cambrian period 45) .…”
Section: Comparison Of Enzymatic Activity Between F-and Cd-exposed Enmentioning
confidence: 76%
“…Our Raman analysis, however, revealed that the replacement of OH with F ions did not occur in rat developing enamel (Table I). This finding may be due to 2 different calcification mechanisms whereby the formation of crystal either with CDL or without CDL is strictly regulated by each hard tissue with the except of pathological calcification 44) . One pathway, mediated by the precursor mineral octacalcium phosphate (OCP), may have appeared around the Cambrian period 45) .…”
Section: Comparison Of Enzymatic Activity Between F-and Cd-exposed Enmentioning
confidence: 76%
“…The stomas present in the surface layer, which were considered to be the marks of odontoblast processes, disappeared during the fossilization. The crystals of dentin and bone possess the CDLbearing crystals [18][19] . Kakei et al reported that the microstructure of apatite crystals might remain considerably stable during the course of fossilization [20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The scientific justification for F therapy for osteoporosis, which induced irregular periosteal bone formation, ligament calcification, abnormal mineralization, and an increase of osteoid formation [29][30][31][32][33][34][35][36], is as follows: Concerning the high dose of F treatment, the increase of bone mineral density might be attributed to the pathological mineralization seen by an abnormal calcification and the presence of large crystals located outside the collagen fibrils [16,17,35,37]. This occurs because a high content of F ions absolutely inhibits the synthesis or activity of certain enzymes such as enolase and carbonic anhydrase [13,14,[38][39][40][41][42]. This might be fatal to cellular metabolism and eventually lead to pathological calcification, which might be similar to the vascular calcification accompanying cellular degeneration [43].…”
Section: Discussionmentioning
confidence: 99%